The Role of Halal Certification Policy in Strengthening Legal Status and Empowering Culinary MSMEs in Indonesia - Dwi Yanti Octaviani; Abdur Rohman (Marasofi International Media and Publishing (MIMP), 2025)
This study aims to assess the contribution of halal certification policy in strengthening the legal status of Micro, Small, and Medium Enterprises (MSMEs), particularly in the culinary sector in Indonesia. Since the enactment of Law No. 33 of 2014 concerning Halal Product Assurance, halal certification has not only become a legal obligation but also serves as a strategic instrument to support the formalization of MSMEs. This research adopts a descriptive qualitative approach through literature review by analyzing various secondary sources such as academic journals, government regulations, and documents related to halal certification and MSME legality. The findings indicate that halal certification policy acts as a key driver in the legalization process of culinary MSMEs, whereby business actors are encouraged to complete other legal documents such as the Business Identification Number (NIB), Home Industry Food Permit (PIRT), and product distribution permits when applying for halal certification. Halal certification provides positive impacts including enhanced product reputation, improved market access, and increased opportunities to obtain formal financing. The Free Halal Certification Program (SEHATI) has proven effective in reducing bureaucratic and financial barriers faced by MSMEs. In conclusion, halal certification has transformed into a strategic asset that not only ensures product compliance with halal standards but also reinforces legal legitimacy and enhances the competitiveness of MSMEs at both national and international levels.